CYTOTOXICITY TEST OF BOVINE DEMINERALIZED BONE MATRIX ON HUMAN MESENCHYMAL STEM CELLS USING THE MTT ASSAY METHOD - Hibono, Paulus Ronald (Journal of Stem Cell Research and Tissue Engineering, 2023)
The use of bone grafts in Indonesia continues to increase each year. Although Autograft is considered the gold standard in bone grafting, its use is often confronted with various challenges, similar to allograft. To address this issue, Bovine Demineralized Bone Matrix (DBM) can be considered as a substitute for bone grafts with the advantages of unlimited availability and more affordable costs. Currently, the Tissue Bank of Dr. Soetomo Hospital is developing bovine DBM, although there is no research yet on its potential toxicity.This study aims to evaluate whether bovine DBM has cytotoxic effects on human mesenchymal stem cells. In this experimental study, a total of 48 samples were involved, including a control group and two treatment groups (50% and 25%), each consisting of 16 samples. Mesenchymal stem cells were cultured and then treated with the addition of 50% and 25% DBM. Subsequently, cell viability was measured using the MTT Assay method.The collected data were processed by conducting normality and homogeneity tests and then analyzed using comparative tests with an independent t-test. The criteria for declaring cell toxicity were set at a viability of not less than 60% compared to the control group.The results of the MTT assay measurements showed that the mean Optical Density (OD) in the control group was 0.656 ± 0.021 (range 0.620-0.696), while in the treatment groups, it was 0.565 ± 0.022 (range 0.529-0.614) and 0.520 ± 0.022 (range 0.461-0.552), respectively. Statistically, the differences in OD between the control group and both treatment groups (50% and 25%) were significant (p<0.05). The average cell viability in both treatment groups was found to be more than 60%, indicating that Bovine Demineralized Bone Matrix is not toxic to human mesenchymal stem cells.